Data User Element DUE Permafrost: a spaceborne permafrost monitoring system - Heim, Birgit; Bartsch, Annett; Elger, Kirsten; Lantuit, Hugues; Boike, Julia; Muster, Sina; Langer, Moritz; Duguay, Claude; Hachem, Sonia; Soliman, Aiman; Paulik, Christoph; Seifert, Frank-Martin (Czech Technical University Prague, 2011)
The task of the ESA Data User Element DUE PERMAFROST project is to build-up an Earth Observation service for permafrost applications with extensive involvement of the permafrost research community. The DUE PERMAFROST remote sensing products are ‘Land Surface Temperature’ (LST), ‘Surface Soil Moisture’ (SSM), ‘Frozen/ Thawed Surface Status’ (Freeze/Thaw), ‘Terrain’, ‘Land Cover’ (LC), and ‘Surface Waters’. A major component is the evaluation of the DUE PERMAFROST products to test their scientific validity for high-latitude permafrost landscapes. There are no standard evaluation methods for this range of remote sensing products, specifically not for these latitudes. Evaluation experiments and intercomparison is done on a case-by-case basis, adding value and experience in validating products for these regions. A significant challenge in the evaluation of remote sensing products for high-latitude permafrost landscapes are the very sparse ground data. We relay on ground data provided by the Users and by international programmes. The primary international programme is the Global Terrestrial Network for Permafrost (GTN-P) initiated by the International Permafrost Association (IPA). Leading projects are the networks of the 'Circumpolar Active Layer Monitoring' (CALM) and the 'Thermal State of Permafrost' (TSP). Prime sites for testing methods and scaling are the long-term Russian-German Samoylov Station in the Lena River Delta (Arctic Siberia), and the tundra and taiga-tundra transition region in Western Siberia (RU). The results of the first evaluations of LST, SSM and Freeze/ Thaw using GTN-P and User’s data show the usability of the DUE PERMAFROST products for high-latitude permafrost landscapes.